P062: SOS: Summer of Smoke--a mixed-methods, community-based study investigating the health effects of a prolonged, severe wildfire season on a subarctic population. (15th May 2017) - Howard, C.; Rose, C.; Dodd, W.; Scott, P.; Cunsulo-Willox, A.; Orbinski, J.
Abstract : Introduction: Between June 15 and Aug 31st 2014, Canada's Northwest Territories (pop 44, 000: Stats Can), a subarctic region which is over 2°C warmer than it was in the 1950's, experienced an unprecedented number of forest fires, with 385 fires and approximately 3.4 million hectares of forest affected. This resulted in one of Canada's most severe and prolonged urban smoke exposures for the capital city of Yellowknife and surrounding Aboriginal communities. Our objective was to obtain a big-picture sense of the health impact of the Summer of Smoke on the population of these communities through a mixture of quantitative and qualitative analysis.Methods: We analyzed PM2.5 levels, salbutamol dispensations, clinic and hospital cardiorespiratory variables, and in-depth video interviews with community members from Yellowknife, N'Dilo, Dettah and Kakisa.Results: 49% of days June15-Aug31 in 2014 had a PM2.5 over 30 mcg/m3, as compared to 3% in 2012 and 9% in 2013 and 2015. Max daily PM 2.5 in 2014 was 320.4 mcg/m3. There was a 22% increase in outpatient salbutamol dispensations in 2014 compared to the average of 2012, 2013 and 2015. More cough, pneumonia and asthma were seen in clinics compared to 2012-2015 (P<0.001). There was a 42% increase in respiratory ER visits in 2014 compared to 2012-13, but no change in cardiac variables. The respiratory effect was most pronounced in children 0-4 (114% increase in ER visits). Qualitative analysis demonstrates themes of fear, isolation, lack of physical activity, alteration of traditional summertime activities for both aboriginal and non-aboriginal subjects, elements of resilience and expectation for future smoky summers in the context of a changing climate.Conclusion: Prolonged wildfire seasons have a profound effect on overall wellbeing. Responses to help minimize mental and physical impacts such as the creation of clean-air community shelters, recreation programming, initiatives to support community cohesion, and "go outside when it is not smoky" messaging require further study.